Basic Life Support Training Method in Undergraduate Nursing Students: a Comparative Research - Dian Ika Puspitasari; Huzaimah, Nailiy (Chakra Brahmanda Lentera Institute, 2023)
Background: Basic life support (BLS) is one of the skills in Emergency Nursing that is a mandatory achievement for undergraduate nursing students. During the past COVID-19 pandemic, the training method changed to an online learning system. This study aimed to determine differences in increasing students' knowledge and skills in carrying out BHD procedures according to the American Heart Association (AHA) 2020 guidelines Methods: This research was a quantitative-experimental pre and post-test design. The population in this study were undergraduate nursing students at the Faculty of Health Sciences, Wiraraja University, in July 2021. Sampling used a simple random sampling technique (n=74), then divided randomly into two groups, the learning group using the offline method (K1; n= 36) and the learning group using the online method (K2; n=38). In this study, the independent variables were BLS knowledge and skill. Data analysis used the Mann-Whitney and Wilcoxon Sign Rank Test because the research data was homogeneous but not normally distributed (α=0.05). Results: The results of the difference test between the two paired groups were p<α; knowledge K1 (0.000), knowledge K2 (0.001), skill K1 (0.002), skill K2 (0.003). Conclusion: The research results showed no difference in knowledge and skills in BHD according to the 2020 AHA guidelines between offline and online learning groups using the simulation method